Effect of draught work on postpartum estrous cycle length in crossbred dairy cows already cycling - Abate, E.; Zerbini, E.; Yami, A.; Mukasa-Mugerwa, E.; Gebre-Wold, A. (Ethiopian Society of Animal Production, 1995)
The study investigated the effect of work on the postpartum estrous cycle length and ovarian activity of crossbred dairy cows used for draught. Sixteen dairy cows were assigned to two dietary feeding regimes (i.e. diet 1=9 MJ ME/kg DM; diet 2=10 MJ/kg DM). The cows in both diets started to work after their second regular estrus, and they were not bred until they showed the fourth estrus. Dry matter intake of cows on diet 2 was greater than for cows on diet 1 during the working and non working periods, eventhough cows on diet 1 increased hay intake during the working period. There was non significant difference in changes in body weight and body condition between cows on both diets. Mean fat corrected milk was greater on diet 2 during resting and working period, but this difference was not significant. First ovulation, first estrus and conception occurred 163 and 239, 180 and 250, and 275 and 343 days, respectively, in cows on diet 2 compared to cows on diet 1. However, differences were not significant. Increase of silent ovulation in supplemented cows during work is probably due to the effect of work stress.